Outpatient service tariff determination based on unit cost analysis mixed with community ability and willingness to pay - Yuniantika; Hendrartini, Julita; Budiarto, Arif (BKM Public Health and Community Medicine, 2023)
Purpose: The study aims to calculate the rational outpatient tariff based on unit cost analysis, ability and willingness to pay. Method: The research is an observational study with a qualitative approach. Secondary data are obtained retrospectively to calculate unit costs and tariffs. Primary data is collected through questionnaires to see the ability and willingness to pay (WTP). Result: The calculation using the step-down method obtained the unit cost for general practice IDR 79,337, dental care IDR 151,635, psychologist consultation IDR 115,283, and fitness center IDR 236,555. The respondent's ATP value is IDR 138,808, with an average examination fee of IDR 56,093. When coupled with an improvement in service and facility quality, 58.1% of respondents agreed to a 10% rate increase. With a 20% rate increase, the willingness to pay decreases to 40.6%. In the bivariate analysis using the chi-square test, the variables significantly affecting WTP are patient perceptions of the suitability of service costs (p = 0.000). In contrast, age, gender, occupation, education, income, number of family members, and insurance ownership do not significantly influence WTP. Conclusion: The service rate is lower than the unit cost calculation. By looking at the ability and willingness to pay, it is possible to evaluate the tariff.